Food hubs for the sustainable short food supply chain in west java - Putri, Rezki Ananda; Handayati, Yuanita (Journal of Business and Management, 2020)
Abstract: This study aims to propose a feasible concept of Food Hubs that can be implemented in West Java for the sustainable short food supply chain and to determine significant differences of value chain of food hub and the existing value chain that implemented in West Java. After analyzing the value chain and mapping the value chain on the existing conditions of the food supply chain in West Java and the supply chain for food hubs, the result is that there is a significant difference between the two chains and the role of food hubs can increase the value of the existing food supply chain in West Java which can assessed by the quality, locality, and sustainability of the supply chain.Keywords: agriculture, food hubs, value chain management, short food supply chain.